Women, the law and the workplace. - Lipschultz, Sybil (Controversies in constitutional law., 2003)
Equal rights for women in the workplace is a critical aspect of the twentieth century civil rights movement, as well as an issue of academic and public interest. Bringing together legal rulings and commentary, this three-volume collection documents the development of legal protections for women in the workplace. The comprehensive coverage encompasses the major legal and constitutional issues, including the legal arguments that lead to the reduction of working hours for women and the argumentation that framed the debates over minimum wage legislation. The set also presents more contemporary iss.